The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1947603519878242
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL2 Promotes Inflammation via Integrin α5β1 in Chondrocytes

Abstract: Background Angiopoietin-like protein 2 (ANGPTL2) is a secreted molecule with numerous physiologic and pathologic functions, for example, in angiogenesis, hematopoiesis, and tumorigenesis. Although recent studies implicated ANGPTL2 in chronic inflammation in mouse peritoneal macrophages, human ligamentum flavum fibroblasts, and human retinal microvascular endothelial cells, the mechanism underlying ANGPTL2-associated inflammation in chondrocytes remains unclear. Therefore, it was investigated whether ANGPTL2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…This cell line presented more similar behavior to human primary chondrocytes in response to pro-inflammatory stimulus than other chondrogenic cell lines. 18,19 First, we observed that IL-1α, a well-known potent inducer of MMP-13, repressed DKK3 expression in chondrocytes, as previously described. 12 Thus, by silencing DKK3 gene, we demonstrated for the first time that DKK3 is acting as a MMP-13 down-modulator in the context of pro-inflammatory cytokine induction, in both human primary chondrocytes and murine ATDC5 cells.…”
Section: Discussionsupporting
confidence: 77%
“…This cell line presented more similar behavior to human primary chondrocytes in response to pro-inflammatory stimulus than other chondrogenic cell lines. 18,19 First, we observed that IL-1α, a well-known potent inducer of MMP-13, repressed DKK3 expression in chondrocytes, as previously described. 12 Thus, by silencing DKK3 gene, we demonstrated for the first time that DKK3 is acting as a MMP-13 down-modulator in the context of pro-inflammatory cytokine induction, in both human primary chondrocytes and murine ATDC5 cells.…”
Section: Discussionsupporting
confidence: 77%
“…This medium induced chondrogenic differentiation, as described previously (Atsumi et al, 1990;Altaf et al, 2006). In our protocol, the gene expression of type II collagen was upregulated strongly 14 days after differentiation induction, however, that of type X collagen was not upregulated yet in ATDC5 Takano et al, 2019). Therefore, we defined the 14-day differentiated ATDC5 as that on the extracellular matrix production stage.…”
Section: Cell Culturementioning
confidence: 93%
“…Total RNA was extracted from each specimen, and cDNA was obtained by reverse transcription (RT) according to previously described methods [ 36 ]. Real-time quantitative RT-PCR was used to evaluate the expression of the following cartilage-specific genes: type II collagen (COL II) a1, Sox-9, aggrecan, and hypertrophic genes: RUNX2, type X collagen (COL X) a1, and MMP13.…”
Section: Methodsmentioning
confidence: 99%